Modified KdV equation for magnetized Rossby waves in a zonal flow of the ionospheric E-layer - Kaladze, T.; Tsamalashvili, L.; Kaladze, D.; Ozcan, O.; Yesil, A.; İnç, Mustafa (Elsevier, 2019)
Nonlinear interaction of magnetized Rossby waves with sheared zonal flow in the Earth's ionospheric E-layer is investigated. It is shown that in case of weak nonlinearity 2D Charney vorticity equation can be reduced to the one-dimensional modified KdV equation. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Nonlinearity; Magnetized Rossby waves; Sheared zonal flow